World Rowing: Covid-19 Pandemic: Advice for training in post-peak and post-pandemic periods - Steinacker, J. M.; Hannafin, J.; Hiura, M.; Wilkinson, M.; Koubaa, D.; Poli, P.; Zupet, P.; Smoljanovic, T.; Bay Nielsen, H. (2020)
Health situation caused by the coronavirus (Sars-cov-2 - covid-19) General information about the pandemic Transmission and safety considerations Infection risk, sport and return to sport Mitigation of risk General information about dealing with covid-infections